Communication between Audiologist, Patient, and Patient’s Family Members during Initial Audiology Consultation and Rehabilitation Planning Sessions: A Descriptive Review - Manchaiah, Vinaya; Bellon-Harn, Monica L.; Dockens, Ashley L.; Azios, Jamie H.; Harn, William E. (Journal of the American Academy of Audiology, 2019)
Communication during clinical consultations is an important factor that facilitates decision-making by patients and family members. For clinicians, these interactions are opportunities to build rapport and to facilitate appropriate decision-making.This article presents the literature review of studies focusing on communication between audiologist, patients, and their family members during initial audiology consultations and rehabilitation planning sessions.A literature review was conducted.The review included eight empirical studies.A systematic search of the CINAHL Complete, MEDLINE, and PsychInfo databases was used to identify relevant articles for review. Quality of the included studies was assessed using the Rating of Qualitative Research (RQR) scale.The average consultation length was 57.4 min (ranged 27.3–111 min), in which the mean length of case history discussion was 8.8 min (ranged 1.7–22.6 min) and the mean length of diagnosis and management planning was 29 min (ranged 2.2–78.5 min). Utterances spoken by audiologists were greater (about 51%) than patients (37%), whereas family members spoke the fewest utterances (12%) during interactions. Patients raised concerns (typically psychological in nature with negative emotional stance) about hearing aids in half of the appointments where hearing aids were recommended as the rehabilitation option. However, audiologists missed opportunities to build relationships as these concerns of patients were not typically addressed. Also, audiologists’ language was associated with hearing aid uptake (i.e., patients were less likely to uptake hearing aids when audiologists used complex language).The review highlights that audiologists dominate the conversation during audiology consultations and rehabilitation planning sessions. Audiologists did not take advantage of the opportunity to develop patient-centered communication and shared decision-making. Implications of these findings to both clinical practice and to audiology education and training are discussed.
Keywords: audiology; clinical consultation; clinician-client communication; communication; conversation analysis; interaction analysis; patient-centered care; psychosocial concerns; shared decision-making